ANALISIS KESULITAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA - D. Kuntuamas, Anatria; Herlina; Muchdar (Universitas Negeri Medan, 2025)
Abstract: This study aims to explore teachers' understanding, planning, and implementation of learning related to the Independent Curriculum at SD Alkhairaat Kotapulu. The research method used is qualitative. The findings reveal that teachers' understanding of the Independent Curriculum is generally good, although further strengthening is needed in practical implementation. Learning planning has adopted the principles of the Independent Curriculum but is hindered by limited facilities. Learning implementation shows positive outcomes with diverse methods and active student engagement, although there are challenges in technology usage. Teachers face difficulties in implementing the Independent Curriculum, including limited facilities, administrative burdens, demands for improved IT skills, and a lack of regular training. This study recommends enhancing teachers' understanding through continuous training, providing adequate facilities, technological support, reducing administrative burdens, and conducting regular curriculum evaluation and adjustments. Keywords: Independent Curriculum, Teacher Understanding, Learning Planning, Learning Implementation, SD Alkhairaat Kotapulu Abstrak: Penelitian ini bertujuan untuk mengetahui pemahaman guru, rencana, dan pelaksanaan pembelajaran terkait Kurikulum Merdeka di SD Alkhairaat Kotapulu. Metode penelitian yang digunakan adalah kualitatif. Hasil penelitian menunjukkan bahwa pemahaman guru terhadap Kurikulum Merdeka tergolong baik, meskipun masih perlu penguatan dalam implementasi praktis. Perencanaan pembelajaran telah mengadopsi prinsip-prinsip Kurikulum Merdeka, namun terkendala keterbatasan fasilitas. Pelaksanaan pembelajaran menunjukkan hasil positif dengan metode beragam dan keterlibatan aktif siswa, meskipun terdapat hambatan dalam penggunaan teknologi. Kesulitan guru dalam implementasi Kurikulum Merdeka meliputi keterbatasan fasilitas, beban administratif, tuntutan peningkatan keterampilan IT, dan kurangnya pelatihan rutin. Penelitian ini merekomendasikan peningkatan pemahaman guru melalui pelatihan berkelanjutan, penyediaan fasilitas yang memadai, dukungan teknologi, pengurangan beban administratif, serta evaluasi dan penyesuaian kurikulum secara berkala. Kata Kunci: Kurikulum Merdeka, Pemahaman Guru, Perencanaan Pembelajaran, Pelaksanaan Pembelajaran, SD Alkhairaat Kotapulu